Analysis of the Influence of ESG Score and Digital Financial Literacy on Company Financial Performance with Corporate Risk-Taking as a Mediating Variable - Supri Yanto; Putri Irmala Sari (Records Management System Journal, 2025)
This study investigates the influence of Environmental, Social, and Governance (ESG) Score and Digital banking Literacy on Financial Performance, with Corporate Risk Taking serving as a mediating variable within the Indonesian banking sector. The research methodology employs a quantitative approach, with samples purposively picked from financial sector businesses listed on the IDX between 2020 and 2024. Data analysis included multiple linear regression approaches, and the mediation effect was assessed using the Baron & Kenny method alongside the Sobel test, processed via SPSS 25 software. The study's findings demonstrate that ESG Score and Digital Financial Literacy significantly enhance the company's Financial Performance. Corporate Risk-Taking is demonstrated to somewhat mediate the association between ESG Score and Financial Performance, and totally mediate the association between Digital Financial Literacy and Financial Performance. This discovery underscores the necessity of incorporating sustainability elements and digital financial literacy into corporate strategy to enhance financial performance via effective risk management. This study enhances financial management literature by amalgamating ESG and digital transformation viewpoints within the framework of corporate risk-taking. The study's added value is the utilisation of Corporate Risk-Taking as a mediating mechanism that elucidates the impact of ESG Score and Digital Financial Literacy on the Financial Performance of financial sector organisations in the digital age.